2008
DOI: 10.1017/s1751731107001085
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Bayes factor analyses of quantitative trait loci for gestation length in Iberian × Meishan F2 sows

Abstract: The aim of this study was to investigate chromosomal regions affecting gestation length in sows. An experimental F 2 cross between Iberian and Meishan pig breeds was used for this purpose and we genotyped 119 markers covering the 18 porcine autosomal chromosomes. Within this context, we have developed a new empirical Bayes factor (BF) approach to compare between nested models, with and without the quantitative trait loci (QTL) effect, and after including the location of the QTL as an unknown parameter in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 42 publications
2
7
1
Order By: Relevance
“…The value was comparable with the mean gestation length in a naturally mated West-type population (113.5 to 114.5 days) (Leenhouwers et al, 1999;Cassady et al, 2002), but longer than in Iberian 3 Meishan F 2 sows (112.16 days), which were mated with artificial insemination (Casellas et al, 2008). Just as the results reported by Sasaki and Koketsu (2007), gestation length had a negative correlation with total number of born piglets.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…The value was comparable with the mean gestation length in a naturally mated West-type population (113.5 to 114.5 days) (Leenhouwers et al, 1999;Cassady et al, 2002), but longer than in Iberian 3 Meishan F 2 sows (112.16 days), which were mated with artificial insemination (Casellas et al, 2008). Just as the results reported by Sasaki and Koketsu (2007), gestation length had a negative correlation with total number of born piglets.…”
Section: Discussionsupporting
confidence: 75%
“…According to the human-pig comparative maps, except the Booroola fecundity gene (BMPR1B) which was related with gilt prolificacy at first parturition (Tomas et al, 2006), there are no other genes associated with animal reproduction near the QTL region. The QTL for gestation length on SSC1, 6, 9, 11 and 15 (Wilkie et al, 1999;Casellas et al, 2008) were not observed in this study. This could be explained by different breeds or genetic background of founder animals in tested F 2 resource populations.…”
Section: Discussioncontrasting
confidence: 71%
See 3 more Smart Citations